Service-oriented computing - icsoc 2019 workshops : wesoacs, asoca, isycc, tbce, and straps, toulouse, france, october 28-31, 2019, revised selected papers /: wesoacs, asoca, isycc, tbce, and straps, toulouse, france, october 28-31, 2019, revised selected papers. (2020) - Unknown
No abstract available